Assessment of Satisfaction with Remuneration for Work: A Case Study of Teachers in a Polish Public Primary School - Agnieszka JUDKOWIAK; Magdalena CHOROŚ (Communications of International Proceedings, 2023)
The aim of this study was to analyze and assess the level of satisfaction among teachers with the remuneration system in place at a public primary school. Data for the research was collected through the use of questionnaires during the year 2023. Based on the findings, it was revealed that a majority of the surveyed teachers expressed dissatisfaction with their current remuneration. Furthermore, the salary increases implemented thus far were deemed insufficient and unsatisfactory by the teachers. The least satisfactory and motivating aspects of remuneration were identified as the basic salary and bonuses. The results of this analysis regarding teachers' satisfaction with their current remuneration may serve as a valuable contribution to future research and aid in the development of an optimal remuneration system that enhances teachers' job satisfaction. The conclusions from the study provide evidence of the need for changes in the teacher remuneration system in Poland.
Keywords: remuneration system; salary; satisfaction; teacher